2017
DOI: 10.1111/bph.13982
|View full text |Cite
|
Sign up to set email alerts
|

Olodaterol shows anti‐fibrotic efficacy in in vitro and in vivo models of pulmonary fibrosis

Abstract: BACKGROUND AND PURPOSEIdiopathic pulmonary fibrosis (IPF) is a fatal respiratory disease characterized by excessive fibroblast activation ultimately leading to scarring of the lungs. Although, the activation of β 2 -adrenoceptors (β 2 -AR) has been shown to inhibit pro-fibrotic events primarily in cell lines, the role of β 2 -adrenoceptor agonists has not yet been fully characterized. The aim of our study was to explore the anti-fibrotic activity of the long-acting β 2 -adrenoceptor agonist olodaterol in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…TGF-β1 is recognized as a focus fibrogenic factor in pulmonary fibrosis, which could promote fibroblast proliferation and collagen deposition. Numerous studies employed TGF-β1 as the pulmonary fibrosis inducer in cell experiments [ 16 , 17 ]. In the present study, to better understand the biological function of miR-1224-5p, we treated fibroblast cell line (NIH/3T3, MRC-5) with various doses of TGF-β1 for 24 and 48 h. We observed that miR-1224-5p levels were significantly increased ( Figure 3 A,B), and α-SMA and Vimentin protein levels were increased compared with those in the control group ( Figure S2A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 is recognized as a focus fibrogenic factor in pulmonary fibrosis, which could promote fibroblast proliferation and collagen deposition. Numerous studies employed TGF-β1 as the pulmonary fibrosis inducer in cell experiments [ 16 , 17 ]. In the present study, to better understand the biological function of miR-1224-5p, we treated fibroblast cell line (NIH/3T3, MRC-5) with various doses of TGF-β1 for 24 and 48 h. We observed that miR-1224-5p levels were significantly increased ( Figure 3 A,B), and α-SMA and Vimentin protein levels were increased compared with those in the control group ( Figure S2A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…4000 primary human lung fibroblasts were seeded per well for α-SMA Western blot replacement and cytotoxicity assays. Determination of α-SMA expression was performed as previously described [33]. In brief, cells were starved in serum-free DMEM for 24 h, pre-treated with different concentrations of Compound 408 for 20 min and stimulated with TGF-β1 (5 ng/ mL) for 48 h. Lysates were assayed in a Western blot replacement assay [Meso Scale Discovery (MSD), Rockville, MD, USA].…”
Section: Methodsmentioning
confidence: 99%
“…Upregulation of COL3A1 is frequently correlated with the fibrotic phenotype of the prostate and an active TGF-β1 signaling pathway [ 9 , 10 , 11 ]. Moreover, downregulation of COL3A1, using anti-fibrotic agents, has been correlated with the attenuation of the fibrotic phenotype in different organs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, COL3A1 could potentially serve as marker for the fibrotic phenotype in the tissues and organs of the pelvis exposed to radiation.…”
Section: Introductionmentioning
confidence: 99%